Clock, David Sassoon Clocktower - Ghosh, Ayan (2023)
The David Sassoon Clock Tower is 67 feet high and has clocks facing the cardinal directions. The clocks are provided with four patent opal glass dials, each measuring four feet in diameter. Unlike other clock towers in Mumbai, which have mostly stopped functioning, the clocks of this clock tower are all in working condition.